RESERVOIR PROPERTIES OF DEEP-SEATED CONSOLIDATED ROCKS OF CARBONIFEROUS PERIOD OF THE CENTRAL GRABEN OF THE DNIEPER-DONETSK DEPRESSION - Vyzhva, S.; Onyshchuk, V.; Onyshchuk, I.; Reva, M.; Shabatura, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Paper concerns the researches of porosity and permeability properties of deep-seated consolidated rocks (siltstones, poor-porous sandstones) of Carboniferous period of the central graben of the Dnieper-Donetsk depression. The purpose of the research was to study the petrophysical parameters of the consolidated reservoir rocks, as the basis of the integrated analysis of their physical properties. Such reservoir parameters as the open porosity factor and void factor, permeability coefficient and residual water saturation factor have been studied. The article presents the limits of changes and the average values of porosity and permeability properties of rocks, and the classification of their reservoir properties. On the basis of capillarimetric research, an evaluation of the structure of the void space of rocks was made. The correlation analysis has allowed establishing a series of empirical relationships between the reservoir parameters (density, porosity coefficient, effective porosity factor and residual water saturation factor) and, also, determining correlation dependences between porosity coefficients measured in atmospheric and reservoir conditions. These relationships can be used in the data interpretation of geophysical studies of wells and in the modeling of porosity and permeability properties of consolidated rocks of the central graben of the Dnieper-Donetsk depression.
Keywords: sandstones; siltstones; porosity and permeability properties; density; porosity coefficient; permeability coefficient; residual water saturation factor; correlation relationships